JENIS - JENIS ANGGREK (Orchidaceae) DI HUTAN SEKUNDER PADA AREAL IUPHHK HTI PT BHATARA ALAM LESTARI KABUPATEN MEMPAWAH - Sarinah, .; Herawatiningsih, Ratna (JURNAL HUTAN LESTARI, 2018)
HTI Area PT. Bhatara Alam Lestari (BAL) is one of the locations that has the potential of orchids. The efforts to conserve the use of orchid species and data collection on the types of orchids need to be done. But the lack of data and information on orchid species identification, the study identified the orchid species in the area.This study aimed to identify orchids (Orchidaceae) nature to the level of the genus. While the benefits were expected to provide information about the existence of orchid species in the protection and preservation efforts could be maintained naturally in the secondary forest IUPHHK-HTI PT. Bhatara Alam Lestari.This research used survey method with exploration and flora collection system. Length of line 500 m, path width 20 m (10 m left and 10 m right). The path was placed by purposive sampling based on the existence of orchids. The results showed 11 species of orchids with 49 individuals from seven genera: Bromheadia, Bulbophyllum, Flickingeria, Coelogyne, Dendrobium, Liparis, Plocogtottis. The largest genus found was Bulbophyllum with four species. The types of orchids found mostly grow on trees (epiphytes) namely: Bulbophyllum macranthum, Bulbophyllum purpurances, Bulbophyllum sp. 1, Flickingeria sp, Coelogyne verucosa, Dendrobium crumenatum, Liparis sp, Coelogyne sp. It was also found growing in the soil (teresterial), namely: Bromheadia finlaysoniana, Bulbophyllum sp. 2, Plocogtottis lowii.Keywords: Bulbophyllum, Epiphytes, Identification, Orchidaceae, Terrestrial.